The association between triglyceride-glucose index and neutrophil-lymphocyte ratio and all-cause mortality in the general US population: NHANES 2001–2018 - Wang, Yifei; Gu, Cheng; Chen, Bingbing; Qiu, Binxu; Yu, Jinhai (Frontiers in Endocrinology, 2024)
The association between the triglyceride-glucose (TyG) index and mortality in the general population remains controversial, with inconsistent findings across studies.This study aims to investigate the relationship between the TyG index and mortality in the U.S. Additionally, it explores whether a new index, combining the TyG index with the neutrophil-to-lymphocyte ratio (NLR), improves the prediction of all-cause compared to the TyG index alone.TyG index were calculated based on participants' complete blood counts and fasting triglyceride and glucose levels. The TyG-NLR index was derived by multiplying the TyG index by the NLR. A weighted Cox proportional hazards model was used to evaluate the associations of the TyG and TyG-NLR indices with mortality risk in the general population. Restricted cubic splines (RCS) were applied to explore and visualize the dose-response relationships between the indices and mortality.This study included 15388 participants. During a median follow-up of 118 months, 2,333 participants died. After adjusting for potential confounders, no significant association was found between the TyG index and mortality. However, compared to the lowest quartile , participants in the highest quartile of the TyG-NLR index showed a significant association with all-cause mortality. Specifically, those in the highest quartile had a 63% higher risk of all-cause mortality .